Mother's Day, May 1987, with two kids she helped raise as their nanny (1987)
Caption affixed to the back reads, 'Mother's Day, 5/87, with two kids she helped raise as their nanny'. In the center of the photo, Alice Martin is wearing a white blouse and a colorful neck scarf, and being embraced by two teenagers. The teenager on the right has short curly brown hair and is wearing a black and white collared shirt. The teenager on the left has a long dark blonde hair, and is wearing a striped baby blue and white shirt. Everyone is seated on leather brown chairs pulled up to what appears to be a dinner table. On the table, there is a plate of food and used pots and pans.